Upaya Meningkatkan Hasil Belajar IPA Pada Materi Interaksi Mahluk Hidup dengan Lingkungan Melalui Model Pembelajaran Picture and Picture di Kelas VII SMP Negeri 8 Kota Bekasi - Hasugian, Rosdiana Seniwarta (Jurnal Gemaedu, 2018)
The purpose of this study is to determine the effectiveness of using Picture and Picture methods in an effort to improve student learning outcomes in science subjects. The subjects of this study were in the 7.3 class with 43 people. In SMP Negeri 8 Kota Bekasi, for 6 months, from January to June 2017. The design of this study uses the method of Stephen Kemmis and Robin M Taggart which consists of 2 cycles, each cycle includes 3 meetings, and each cycle includes 4 steps namely planning, implementation, observation, and reflection. Indicators of success are seen from increasing understanding of concepts, activeness, and learning outcomes of students. The instruments used in this study were test questions, and classroom observations. The results showed an increase in learning outcomes after Classroom Action Research. In the first cycle, it was seen from 43 students in the 7.3 class who achieved KKM of 76 as many as 33 students with 76% completeness. And we see the improvement in learning outcomes in cycle 2, out of 43 students in the 7.3 class who achieved KKM of 76 as many as 39 students with 91% completeness.